2022
DOI: 10.3390/fishes7060398
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Different Routes of Formalin-Killed Vaccine Administration on Immunity and Disease Resistance of Nile Tilapia (Oreochromis niloticus) Challenged with Streptococcus agalactiae

Abstract: Vaccines prepared from formalin-killed Streptococcus agalactiae were administered to Nile tilapia (Oreochromis niloticus) via three different routes: immersion in a water-based vaccine, injection with an oil-based vaccine, and as a water-based oral vaccine. All vaccination treatments increased lysozyme and peroxidase activity in skin mucus of Nile tilapia by 1.2- to 1.5-fold compared to their activities in unvaccinated control fish. Likewise, alternative complement, phagocytosis, and respiratory burst activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…These results correlate to the levels of antibody production in each of the vaccinated groups, where the fish immunized with the heat-killed bacteria emulsified in adjuvant presented significantly higher levels of antibodies throughout the 14 months of the experiment, compared to the fish immunized with the heat-killed bacteria + PBS. Many studies have been conducted toward the improvement of vaccine performance such as capturing the antigens in liposomes, or the addition of adjuvants to lead to better immunomodulation and increase protection [16,[41][42][43]. Adjuvants are essential elements that increase the efficacy of vaccination practices through many different actions such as stimulators of immune responses [30,44].…”
Section: Discussionmentioning
confidence: 99%
“…These results correlate to the levels of antibody production in each of the vaccinated groups, where the fish immunized with the heat-killed bacteria emulsified in adjuvant presented significantly higher levels of antibodies throughout the 14 months of the experiment, compared to the fish immunized with the heat-killed bacteria + PBS. Many studies have been conducted toward the improvement of vaccine performance such as capturing the antigens in liposomes, or the addition of adjuvants to lead to better immunomodulation and increase protection [16,[41][42][43]. Adjuvants are essential elements that increase the efficacy of vaccination practices through many different actions such as stimulators of immune responses [30,44].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported the development of effective vaccines against S. agalactiae infection in Nile tilapia [ 13 , 30 , 31 , 32 , 33 ]. The results obtained for most developed vaccines showed that they were very effective in the laboratory [ 34 , 35 , 36 ] and on the field-trial scale [ 37 , 38 , 39 ], but most of those studies relied on injection methods [ 40 , 41 , 42 ]. This vaccination route was subsequently found to be impractical and unacceptable for field application in many fish species.…”
Section: Discussionmentioning
confidence: 99%
“…The S.pyogenes antigen was prepared according to (Nguyen et al, 2022), then lyophilized and measured the protein concentration by Biuret method (Randox Lab). It was kept under 4 o C in a refrigerator until use as antigen in experimental rats, when used re-suspended by adding 2 ml of Phosphate buffer saline PBS to 2 gm of dry lyophilized antigen to make stock solution according to (Rafeek et al, 2021).…”
Section: Preparation Of Streptococcus Pyogenes Antigenmentioning
confidence: 99%